2018
DOI: 10.1002/bdr2.1208
|View full text |Cite
|
Sign up to set email alerts
|

Potential genetic markers for nonsyndromic oral clefts in the Brazilian population: A systematic review and meta‐analysis

Abstract: A large number of genetic markers distributed in several genes/loci was associated with NOC in the Brazilian population, but in general the original studies included limited number of samples and unsatisfactory protocols. The classical risk markers located in IRF6 and 8q24 showed promising results as well as rs1801133 in MTHFR and rs17563 in BMP4, and they should be validated in larger and multicenter studies taking in consideration the variations in the miscegenation of Brazilian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 99 publications
1
30
0
1
Order By: Relevance
“…As the proportion of African ancestry of the Brazilian population affects the genetic susceptibility to NSCL±P [Brito et al, ; Bagordakis et al, ; de Aquino et al, ; do Rego Borges et al, ; Messetti et al, ; Machado et al, ], and the frequency of risk alleles at some of selected SNP differ according to ethnicity, specially between African and Caucasian populations, we performed similar analyses in the subgroups of samples showing high European ancestry and high African ancestry. In the subgroup with high European ancestry, the average of European ancestry was higher than 90% in both groups (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the proportion of African ancestry of the Brazilian population affects the genetic susceptibility to NSCL±P [Brito et al, ; Bagordakis et al, ; de Aquino et al, ; do Rego Borges et al, ; Messetti et al, ; Machado et al, ], and the frequency of risk alleles at some of selected SNP differ according to ethnicity, specially between African and Caucasian populations, we performed similar analyses in the subgroups of samples showing high European ancestry and high African ancestry. In the subgroup with high European ancestry, the average of European ancestry was higher than 90% in both groups (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As 2017; Machado et al, 2018], and the frequency of risk alleles at some of selected SNP differ according to ethnicity, specially between African and Caucasian populations, we performed similar analyses in the subgroups of samples showing high European ancestry and high African ancestry. In the subgroup with high European ancestry, the average of European ancestry was higher than 90% in both groups ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies investigating IRF6 in the context of NSCLP have produced controversial results. While some studies identified IRF6 mutations and polymorphisms associated with the disorder, others did not identify any IRF6 mutations associated with non‐syndromic cleft lip and/or palate pathogenesis (Assis Machado et al, ; Brito et al, ; Butali et al, ; Cuddapah, Kominek, Grant, & Robin, ; de Souza et al, ; Desmyter et al, ; do Rego Borges, ; Jehee et al, ; Khandelwal et al, ; Larrabee et al, ; Leslie et al, ; Paranaiba et al, ; Pegelow et al, ; Rutledge, Barger, Grant, & Robin, ).…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of NOC is approximately 1:700 live births (Dixon, Marazita, Beaty, & Murray, ), but in Brazil, with considerable geographic variation, the prevalence ranges from 1:650 to 1:2,700 live births (Martelli‐Junior et al, ; Rodrigues, Sena, Roncalli, & Ferreira, ). NOC etiology is recognized as complex and heterogeneous, and though our understanding behind this malformation is evolving, the exact environmental and genetic risk factors associated remains not fully defined (Assis Machado et al, ; Beaty, Marazita, & Leslie, ). Many studies have supported the participation of maternal contact with agrotoxics, smoking, alcohol and some drugs, and folate supplementation during early pregnancy as the main environmental factors related to NOC etiology (Molina‐Solana, Yáñez‐Vico, Iglesias‐Linares, Mendoza‐Mendoza, & Solano‐Reina, ; Spinder et al, ; Xiao, Liu, Liu, Zhang, & Xue, ; Xuan et al, ).…”
Section: Introductionmentioning
confidence: 99%